ADYGHE OF THE NORTHWEST CAUCASUS AMID REGIONAL POLITICAL SHIFTS (1820-1880) - Kudaeva, Svetlana Grigor'evna (History, Archeology and Ethnography of the Caucasus, 2024)
One hundred and sixty years have passed since the tragic events in the Northwest Caucasus that shaped the current state of the Adyghe (Circassian) ethnic group. Today, the Adyghe diaspora far exceeds the population remaining in their historical homeland, raising numerous questions. The most pressing of these concerns is the underlying causes behind this demographic shift. This study examines Adyghe emigration from a new perspective, spanning the three Russian-Turkish wars of the 19th century (1828-29, 1853-56, 1877-78). During this period, fundamental changes occurred in the ethnolocalization, quantitative, and ethnic composition of the autochthonous population of the North-West Caucasus. This research focuses on how the political dynamics altered depending on the outcomes of these wars, the terms of peace treaties, and their impact on state policies regarding Adyghe emigration. This approach aims to reinforce the evidence base of existing conclusions in Russian Caucasian studies. The study employs principles of scientificity, historicism, and objectivity as its methodological foundation, alongside historical research methods such as retrospective analysis and specific analysis. It concludes that the outcomes of the Russian-Turkish wars significantly influenced the political landscape, driving state policies that altered the migration processes and fundamentally changed the ethnolocalization of the Adyghe ethnic group.